Study on the Relationship between Coal Consumption and Economic Growth: Based on the Data from 1981-2011 of China - Li, Li; Lei, Yalin; Pan, Dongyang (Journal of Environmental Accounting and Management, 2026)
Coal continues to play an important role in the world and in China in the future. Although renewable energy will obtain a bigger development, coal is still one of the main characters in the pattern of world energy in the next 30 years. Using vector error correction model and the data from 1981- 2011 in China, the paper examines the relationship between the variables coal consumption and economic growth for China. The results show that there is a bi-directional granger causality relationship between coal con sumption and economic growth in the short and long run in China, which means that rapid economic growth promotes huge coal consumption, and coal consumption supports economic growth.